Impact of Global SST on Decadal Shift of East Asian Summer Climate - 付建建 李双林 罗德海 (Advances in atmospheric sciences, 2009)
East Asia experienced a significant interdecadal climate shift around the late 1970s, with more floods in the valley of the Yangtze River of central-eastern China and more severe drought in North China since then. Whether global SST variations have played a role in this shift is unclear. In the present study, this issue is investigated by ensemble experiments of an atmospheric general circulation model （AGCM）, the GFDL AM2, since one validation reveals that the model simulates the observed East Asian Summer Monsoon （EASM） well. The results suggest that decadal global SST variations may have played a substantial role in this climate shift. Further examination of the associated atmospheric circulation shows that these results are physically reasonable.